Nitrogen uptake by malting barley grown under conditions found in Buenos Aires Province, Argentina - Lazzari, Maria Aurora (2007)
There is a lack of data associated with applications of nitrogen (N) fertilizer to increase yield while not increasing seed protein to levels exceeding those acceptable for malting barley (Hordeum vulgare L.) in the Buenos Aires province of Argentina. The effect of rates and timing of N application on yield and grain N concentration of malting barley was evaluated at eight sites in 1999 and 2000. Aboveground dry matter accumulation and N-uptake pattern through the growing season were evaluated. Dry matter production and N-uptake were measured at four sampling times: tillering, head emergence, grain filling, and maturity. The N fertilizer increased grain yield, but its response varied between sites. Under appropriate conditions, the yield increased and maintained the grain N concentration within a desirable range for malting barley. Split applications were as effective in increasing grain yield as one addition at emergence, but they invariably increased grain N concentration. The season affected the yield response to N fertilizer and its levels in the grain, but the nitrogen harvest index was not affected by the rate of N application.